2021
DOI: 10.21203/rs.3.rs-625377/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Novel Ferroptosis-Related Lncrnas Signature for Prognosis Prediction in Patients with Papillary Renal Cell Carcinoma

Abstract: BackgroundPapillary renal cell carcinoma (PRCC) is a common renal cell carcinoma. Recent studies have reported that ferroptosis is involved in the occurrence and development of tumors. Long non-coding RNAs could be used as independent biomarkers for the diagnosis and prognosis of a variety of tumors, and many lncRNAs are related to the pathogenesis of PRCC. However, there are few studies on the ferroptosis-related lncRNAs of PRCC. This study aimed to establish ferroptosis-related lncRNAs prognostic signature i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…AC022075.1 is a ferroptosis‐related lncRNA downregulated in BAR‐T PGA + ATP4AB cells. Differential expression of AC022075.1 may be associated with overall survival in patients with papillary renal cell carcinoma 67 . We have already demonstrated that MT1G, a protein‐coding ferroptosis gene, is upregulated in BAR‐T PGA + ATP4AB cells.…”
Section: Discussionmentioning
confidence: 95%
“…AC022075.1 is a ferroptosis‐related lncRNA downregulated in BAR‐T PGA + ATP4AB cells. Differential expression of AC022075.1 may be associated with overall survival in patients with papillary renal cell carcinoma 67 . We have already demonstrated that MT1G, a protein‐coding ferroptosis gene, is upregulated in BAR‐T PGA + ATP4AB cells.…”
Section: Discussionmentioning
confidence: 95%